"I Find It Really Difficult to Control Myself Too": A Qualitative Study of the Effects on the Family Dynamic When Parent and Child Have ADHD - Kate Carr-Fanning; Conor McGuckin (MDPI AG, 2022)
If having one child with Attention Deficit Hyperactivity Disorder (ADHD) contributes to family stress and dysfunction, then what happens when more than one family member has ADHD? This paper explores this question by drawing on findings from a multi-case study that explored the voices of stakeholders (child and parent/carer) affected by ADHD in Ireland. There were eight case studies (families) included. Each case had one parent/carer with ADHD and a child with ADHD. Eight children (aged 7-17 years; Mean = 12.6; S.D. = 3.4) and ten parents (2 males) participated. Four parentw/carers reported a diagnosis of ADHD themselves (2 females) and 6 mothers participated who had a spouse with ADHD. Triangulation was achieved using multiple interviews (parent/carers and child), a demographic survey, and creative methods with the children to contribute to a highly contextualised understanding of stakeholders' experiences. Research findings demonstrated that there may be positive and negative consequences when both parent and child have ADHD. On the one hand, it may contribute to greater dysfunction, when parents with ADHD struggle to stick to routines and remain calm and organised. On the other hand, children with ADHD may feel a sense of belonging and less different, parents believe they have greater understanding, and shared interactional preferences may have benefits. Findings will be discussed in terms of their implications for practice with families and future research.